2008
DOI: 10.1021/bm701111z
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of an Amphiphilic Silk-Like Polymer

Abstract: An amphiphilic silk-like protein polymer was efficiently produced in the yeast Pichia pastoris. The secreted product was fully intact and was purified by solubilization in formic acid and subsequent precipitation of denatured host proteins upon dilution with water. In aqueous alkaline solution, the negatively charged acidic polymer assumed extended helical (silk III-like) and unordered conformations. Upon subsequent drying, it assumed a conformation rich in beta-turns. In water at low pH, the uncharged polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 38 publications
3
73
1
Order By: Relevance
“…384 This observation was attributed to the slow crystallization of the PFS-core in protic polar solvents. 385 Due to the kinetic stability of the cylindrical micelles the Winnik and Manners groups have been able to build increasingly sophisticated superstructures with multiple levels of structural hierarchy, for example the gradient CDSA into cylindrical comicelles with segmented coronas, 386 the self-assembly of the multiblock comicelles into nanofibrillar hydrogels, 387 [394][395][396][397][398][399][400][401] In most of the reported examples these triblocks consist of a central silk inspired [402][403][404][405][406][407][408][409] repeat of (GAGAGAGX) n (where X 5 E, K, or H; n 5 48), which are flanked by two hydrophilic and inert collagen-based blocks that are dimers of the triplet repeat (GXY) n (where X and Y are rich in Q, N, and S; n 5 99) (Fig. 31).…”
Section: Living Supramolecular Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…384 This observation was attributed to the slow crystallization of the PFS-core in protic polar solvents. 385 Due to the kinetic stability of the cylindrical micelles the Winnik and Manners groups have been able to build increasingly sophisticated superstructures with multiple levels of structural hierarchy, for example the gradient CDSA into cylindrical comicelles with segmented coronas, 386 the self-assembly of the multiblock comicelles into nanofibrillar hydrogels, 387 [394][395][396][397][398][399][400][401] In most of the reported examples these triblocks consist of a central silk inspired [402][403][404][405][406][407][408][409] repeat of (GAGAGAGX) n (where X 5 E, K, or H; n 5 48), which are flanked by two hydrophilic and inert collagen-based blocks that are dimers of the triplet repeat (GXY) n (where X and Y are rich in Q, N, and S; n 5 99) (Fig. 31).…”
Section: Living Supramolecular Polymerizationmentioning
confidence: 99%
“…These were studied in great detail using CD and FT-IR spectroscopy, TEM, cryo-TEM, AFM, SLS, SAXS, and rheometry. 394,[396][397][398]400,401 Intriguingly, the self-assembly was found to take place only on one side of the growing fibrils, and these ends remain reactive if all unimer is consumed [ Fig. 31(c,d)].…”
Section: Living Supramolecular Polymerizationmentioning
confidence: 99%
“…9 Werten et al biosynthesized an amphiphilic silk-like polypeptide rendering hydrophobic surfaces hydrophilic, and hydrophilic surfaces hydrophobic. 10 Wang et al biosynthesized and characterized the typical fibroin crystalline polypeptides of silkworm B. mori, and they demonstrated that the hexapeptide (GAGAGS) was the key basis to form bsheet conformation in the silk fibroin crystalline domain. 11 Yamamoto et al obtained a silk-like poly(amino acid) fiber at aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Several successful laboratory-scale E. coli fermentation processes have been reported [47,[52][53][54][55][56][57][58][59][60][61][62], although instable DNA fragments [47][48][49], low yields [47,49], accumulation in inclusion bodies [63] and generally low protein solubility [52,54,59,[64][65][66] have been reported. The methylotrophic yeast Pichia pastoris has been used with the purpose to minimize truncations due to translation stops [67] and to allow extracellular secretion, which has been shown to occur for an amphiphilic silk-like protein [68]. Expression in various plants (tobacco, potato, Arabidopsis) has been tried as an alternative approach aimed at efficient and cheap production suitable for scale-up.…”
Section: Recombinant Spidroin Productionmentioning
confidence: 99%